Evolving Standards for Academic Publishing: A q‐r Theory - Ellison, Glenn (Journal of Political Economy, 2002)
This paper develops models of quality standards to examine two trends: academic journals increasingly require extensive revisions of submissions, and articles are becoming longer and changing in other ways. Papers are modeled as varying along two quality dimensions: q reflects the importance of the main ideas and r other aspects of quality. Observed trends are regarded as increases in r-quality. A static equilibrium model illustrates comparative statics explanations. A dynamic model in which referees (with a biased view of their own work) learn social norms for weighting q and r is shown to produce a long, gradual evolution of social norms.